Investigation of fever in the eastern borders of Kollam district, Kerala, India - Gopakumar, Soumya; Scaria, Sonia; Thomas, Achu; Nujum, Zinia T.; Mohan, Devi (International Journal Of Community Medicine And Public Health, 2018)
Background: The state of Kerala is endemic for Dengue. The district Kollam in Kerala reported increasing fever trend as per the state surveillance report. So an investigation was planned to estimate the burden of fever in the locality of reported Dengue cases, to calculate vector indices around areas of confirmed cases and to study the clinical profile and risk factors of Dengue fever. Methods: A Cross sectional survey with entomological survey was conducted in houses around the confirmed dengue cases. A case control analysis was done with Dengue positive as cases and negative test results among the fever cases as controls .Odds ratio was calculated for strength of association and statistical test of significance using Chi Square test. Results: Total number of households visited was 80, numbers of hospitalized patients were 26.Total fever cases studied were 46 of which 30.4% and 8.7% were positive for IgM and IgG Dengue respectively.PCR was positive in 28.3%. Chills [OR – 3.55 (1.05-12.1)], p value < 0.03, was found to be significantly associated with Dengue positivity .Dengue positivity was higher among housewives, but not found to be statistically significant. 51.2% of the households had water storage containers at home. Breteau index in one of the areas surveyed was 60 and 52. Conclusion: More awareness needed to be generated among the public of the importance of identifying and destroying the vector breeding sites around households as very often breeding sites are found right inside houses.